Penggunaan Platform Game Education dalam Pendidikan Keperawatan: Kajian Literatur - Boby Nurmagandi (ARTERI : Jurnal Ilmu Kesehatan, 2019)
Development of information and communication technology that increases complexity in the education system where the learning process develops to be electronic-based, the use of electronic-based learning systems in nursing education provides an interesting development for students. one of them is the use of educational game platforms. The use of educational game platforms can provide convenience in learning the learning system. The method of reading this article is the Study of Literature Review through searching articles on 2 data-based, namely: Science Direct and Scopus. The inclusion criteria for this literature study are full text free, waiting for English, and published 2013-2018. The keywords used in the search article are Games, Educational Games, Platform Educational Games, Nursing Educational Games. search results found 294 articles starting with reading the title and abstract sections to find 10 articles that are relevant for use for literature review. The results of the conclusions study concluded that the use of educational game platforms in the learning process can increase learning interest, student satisfaction levels, increase self-efficacy, the level of punishment and the ability to make decisions. The use of educational games can also increase student learning prose, create active learning arrangements, easy to understand learning material, and improve students' clinical teaching skills. Educational games related to educational game platforms, collaboration between education and related parties Industrial games to educate game platforms according to the needs in the learning process.